SELF ASSESSMENT TO KNOW UNDERSTANDING MATHEMATIC CONCEPT - Deni Iriyadi (Universitas Sembilanbelas November Kolaka, 2018)
This research is a qualitative study aimed to determine the students' understanding of the concept of matter limit. The subjects were students of class XI IPA 1 SMA Negeri 1 Watampone. The concept includes the definition of the limit. Data obtained using a research instrument in the form of self-assessment and then proceed with the interview subjects were selected based on the results of self-assessment has been done before. Analysis using qualitative analysis of students' understanding of the concept of the limit concept. The results of this study indicate that students' understanding of concepts some of which are not / do not understand especially regarding definitions limit. In addition students are also wrong about the resolution limit. Students who understand the concept of limit dinyakatakan them restate concepts, including examples and classify the sample to non-completion of function and limit the right results.